2001
DOI: 10.1080/00071660120055304
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between shell colour and ultrastructure in pheasant eggs

Abstract: 1. The histochemistry and ultrastructure of pheasant eggs were compared on the basis of blue or brown shell colour. 2. Differences in lectin histochemistry of the outer shell membrane calcification surface indicate a biochemical disruption of the calcification sites in blue eggs. 3. Significant differences were observed in all aspects of eggshell ultrastructure with blue eggs having thinner shells with structural defects. 4. Poor hatchability of blue eggs may reflect high rates of weight loss associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Support for this hypothesis stems from the biochemical properties of protoporphyrin (Gosler et al ) as well as a negative correlation between protoporphyrin and eggshell thickness, with multiple lines of evidence suggesting that birds that are calcium‐limited may use protoporphyrin to compensate for necessarily thinner eggshells (Cherry and Gosler , Gosler et al ). While previous studies have shown no significant link between blue‐green eggshell coloration and eggshell thickness (Jagannath et al ), other studies have documented such relationships, with bluer eggshells sometimes having thinner (Richards and Deeming ) or thicker (Morales et al ) eggshells (but see Cassey et al ). However, these studies all examined relationships between eggshell thickness and blue‐green coloration, but not with biliverdin concentration per se.…”
Section: Discussionmentioning
confidence: 96%
“…Support for this hypothesis stems from the biochemical properties of protoporphyrin (Gosler et al ) as well as a negative correlation between protoporphyrin and eggshell thickness, with multiple lines of evidence suggesting that birds that are calcium‐limited may use protoporphyrin to compensate for necessarily thinner eggshells (Cherry and Gosler , Gosler et al ). While previous studies have shown no significant link between blue‐green eggshell coloration and eggshell thickness (Jagannath et al ), other studies have documented such relationships, with bluer eggshells sometimes having thinner (Richards and Deeming ) or thicker (Morales et al ) eggshells (but see Cassey et al ). However, these studies all examined relationships between eggshell thickness and blue‐green coloration, but not with biliverdin concentration per se.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the results obtained for hatchability and the hatchability of fertile eggs in the present study diverged from those reported by Farghly et al (2015) and Hassan et al (2013) suggesting eggshell colour to have an effect on both hatchability and hatchability of fertile eggs. In research conducted by Hulet et al (1985) and Richards and Deeming (2001) on pheasant eggs, it was ascertained that blue and tan coloured eggs had a thinner eggshell and presented a lower hatchability, in comparison with green, dark brown, and grey/white eggs. Furthermore, Kożuszek et al (2009a) reported that the hatchability of fertile eggs was lower in blue eggs compared with dark brown eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Hulet et al (1978) demonstrated that, in pheasant eggs, eggshell colour and hatchability were correlated with each other. Richards and Deeming (2001) suggested that eggs with blue eggshell colour are structurally defective eggs with a thin eggshell. These researchers explained the low hatchability of blue coloured eggs as being due to the high weight loss resulting from their structural defection.…”
Section: Introductionmentioning
confidence: 99%
“…Brown eggshell color has been positively correlated with some shell characteristics such as shell strength and hatchability (Sekeroglu and Duman, 2011), while egg internal quality has no correlation with shell color (Yang et al, 2009). Further, it has been suggested that some shell quality parameters such as shell strength, shell weight, shell thickness, and shell ultrastructure can be assessed via shell color because of significant correlations between the shell quality indicator and shell color (Schreiweis et al, 2006;Yang et al, 2009); however, others have provided conflicting evidence (Joseph et al, 1999;Richards and Deeming, 2001), and thus shell color cannot be applied reliably as a quality assessment tool.…”
Section: Shell Color and Egg Qualitymentioning
confidence: 99%